Early modern overseas trade and entrepreneurship : Nordic trading companies in the seventeenth century - Wirta, Kaarle (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Drawing on an impressive range of archival material, this monograph delves into the careers of two businessmen who worked for Nordic chartered monopoly trading companies to illuminate individual entrepreneurship in the context of seventeenth-century long-distance trade. The study spans the Caribbean to the Indian Ocean, examining global entanglements through personal interactions and daily trading activities between Europeans, Asian merchants and African brokers. It makes an important contribution to our understanding of the role of individuals and their networks within the great European trading companies of the early modern period. This unique book will be of interest to advanced students and researchers of economic history, business history, early modern global history and entrepreneurship"--
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship -- Scandinavia -- History -- 17th century; Scandinavia -- Commerce -- History -- 17th century; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Economics / General